INSERSI GEN pncA KE DALAM PLASMID pGEM-T - Eli Hendrik Sanjaya (Universitas Airlangga, 2016)
Abstract. Multidrug-resistant tuberculosis (MDR-TB) is among the most worrisome elements of the pandemic of antibiotic resistance. As the first line drug, pyrazinamide is often used to treat TB desease so there are many case of TB resistant to pyrazinamide. The previous research show that pncA gene of isolate L20 MDR-TB have mutated T539C. That mutation propose as the cause of resistance M. tuberculosis to pyrazimanide at the genetic level. For make sure the resistance mechanism, we have to get the pure PZAse and crystalization so the 3D structure can be determined by X-ray defraction. The first step to get the pure PZAse is cloning the pncA gene to the plasmid. The aim of this research is to know that is the pncA gene can be cloned to pGEM-T plasmid. The prosedure for cloning the pncA gene to the pGEM-T plasmid is amplification, followed by insert the pncA gene to the pGEM-T plasmid, and transformation by a selection of blue and white colony. The last step are isolation plasmid recombinant (pGEM-T-pncA) followed by electrophoresis. The result of the research showed that pncA gene from isolate L20 was successfully cloned to pGEM-T plasmid. That was showed on blue and white colony and the result of isolation and electrophoresis pGEM-T-pncA. The electrophoregram showed that the length of pGEM-T-pncA from white colony is different with pGEM-T standart abaut 0,7 kb. It is similar with the length of pncA gene (0,72 kb). Keywords: kloning, pGEM-T, pncA gene, pyrazinamide (PZA).